Resolving Atomic Connectivity in Graphene Nanostructure Junctions - Dienel, Thomas; Kawai, Shigeki; Soede, Hajo; Feng, Xinliang; Muellen, Klaus; Ruffieux, Pascal; Fasel, Roman; Groening, Oliver (Nano Letters, 2015)
We report on the structural characterization of junctions between atomically well-defined graphene nanoribbons (GNRs) by means of low-temperature, noncontact scanning probe microscopy. We show that the combination of simultaneously acquired frequency shift and tunneling current maps with tight binding (TB) simulations allows a comprehensive characterization of the atomic connectivity in the GNR junctions. The proposed approach can be generally applied to the investigation of graphene nanomaterials and their interconnections and is thus expected to become an important tool in the development of graphene-based circuitry.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene nanoribbon; nc-AFM; noncontact atomic force microscopy; scanning tunneling microscopy; tight binding; Two-dimensional material